Effects of compression clothing on speed-power performance of elite Paralympic sprinters: a pilot study - Loturco, I.; Winckler, C.; Lourenço, T. F.; Verissimo, A.; Kobal, R.; Kitamura, K.; Pereira, L. A.; Nakamura, F. Y. (SpringerPlus, 2016)
Compression garments are thought to aid performance in some selected speed-power activities owing to improved sensory feedback and proprioception. The aim of this study was to test the effects of using compression garments on speed and power-related performances in elite sprinters with visual impairment, who rely more on proprioception to perform than their Olympic peers. Eight top-level Paralympic sprinters competing in 100- and 200-m races performed, in the following order: unloaded squat jump (SJ), loaded jump squat (JS) and sprint tests over 20- and 70-m distances; using or not the compression garment. The maximum mean propulsive power value obtained during the JS attempts (starting at 40 % of their body mass, after which a load of 10 % of body mass was progressively added) was considered for data analysis purposes. The athletes executed the SJ and JS attempts without any help from their guides. Magnitude-based inference was used to analyze the results. Findings: The unloaded SJ was possibly higher in the compression than the placebo condition (41.19 ± 5.09 vs. 39.49 ± 5.75 cm). Performance differences in the loaded JS and sprint tests were all rated as unclear. Conclusions: It was concluded that the acute enhancement in vertical jump ability should be explored in the preparation of Paralympic sprinters during power-related training sessions. However, chronic effects in Paralympic athletes wearing compression garments need to be further tested, in order to support its use as a specific training aid.